COMPARISON OF THE PERFORMANCE OF SHARIA BANKS AND CONVENTIONAL BANKS - Faradilla Felysha (RADJA PUBLIKA, 2023)
This study aims to find out and analyze the significant differences between the performance of conventional banks and Islamic banks and to find out and analyze which banking performance is better between Islamic and conventional banking. This study uses a qualitative descriptive method using secondary data. From the results of the study there is a significant difference between conventional banking and Islamic banking such as the absence of interest in Islamic banking considering that interest is forbidden in Islamic law as usury. Furthermore, in terms of risk in conventional credit, the customer still has to pay the full loan and interest as previously agreed. Both when the business makes a profit or loss while sharia credit if the contract used is capital sharing,